2021
DOI: 10.48550/arxiv.2104.02068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First Analysis of Jupiter in Gamma Rays and a New Search for Dark Matter

Abstract: We present the first dedicated gamma-ray analysis of Jupiter, using 12 years of data from the Fermi Telescope. We find no robust evidence of gamma-ray emission, and set upper limits of ∼ 10 −9 GeV cm −2 s −1 on the Jovian gamma-ray flux. We point out that Jupiter is an advantageous dark matter (DM) target due to its large surface area (compared to other solar system planets), and cool core temperature (compared to the Sun). These properties allow Jupiter to both capture and retain lighter DM, providing a compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 66 publications
0
40
0
Order By: Relevance
“…Finally, note that some recent works did not follow these arguments and incorrectly estimated the DM evaporation mass [30,32,68,75,94]. In Ref.…”
Section: Ii5 Dm Evaporation Mass: a Tale Of Two Tailsmentioning
confidence: 98%
See 2 more Smart Citations
“…Finally, note that some recent works did not follow these arguments and incorrectly estimated the DM evaporation mass [30,32,68,75,94]. In Ref.…”
Section: Ii5 Dm Evaporation Mass: a Tale Of Two Tailsmentioning
confidence: 98%
“…The DM evaporation mass has been computed at different levels of detail for the case of the Sun [2, 3, 5-7, 10, 19, 21, 64-67], but has been less studied for other celestial bodies. Some examples, however, are the calculations for the Earth [18,19,23,31], the Moon [31], Mars [30], giant planets [32,68], brown dwarfs [32,33], main-sequence stars [33,69], horizontal-branch stars [49,70], and neutron stars [71,72].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, DM may annihilate into new long-lived mediators which can escape the Sun and decay into SM particles outside the Sun [24][25][26][27][28][29]. It is also shown that Jupiter can be a viable DM target especially for sub-GeV DM owing to its cooler core temperature compared to the Sun [30]. These scenarios are realized in the context of secluded DM models.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, if DM thermalizes slowly with the NS, annihilations may turn on late, so that there are two reheating periods in our "infrequent encounter" regime. DM annihilations following capture of subhalo DM could also produce detectable signals in a variety of celestial bodies [77,[111][112][113]. While we have focused on DM-nucleon scattering, some of our approaches also apply to DM that scatters on leptons.…”
mentioning
confidence: 99%